2020
DOI: 10.1002/nag.3057
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional hydromechanical modeling of internal erosion in dike‐on‐foundation

Abstract: Currently, numerical studies at the real scale of an entire engineering structure considering internal erosion are still rare. This paper presents a threedimensional (3D) numerical simulation of the effects of internal erosion within a linear dike located on a foundation. A two-dimensional (2D) finite element code has been extended to 3D in order to analyze the impact of internal erosion under more realistic hydromechanical conditions. The saturated soil has been considered as a mixture of four interacting con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 62 publications
1
21
0
Order By: Relevance
“…34 Table 2 summarizes the properties of particles and fluid and numerical settings in the simulations. To achieve numerical stability for CFD and DEM domain, the Courant number, defined in Equation 13, should be below 0.2 and the time step for DEM domain should be determined by the method proposed by Cundall and Strack 40 as seen in Equation (14). where Δt f is the fluid timestep and Δl is the minimum fluid cell length.…”
Section: Simulation Programmentioning
confidence: 99%
See 2 more Smart Citations
“…34 Table 2 summarizes the properties of particles and fluid and numerical settings in the simulations. To achieve numerical stability for CFD and DEM domain, the Courant number, defined in Equation 13, should be below 0.2 and the time step for DEM domain should be determined by the method proposed by Cundall and Strack 40 as seen in Equation (14). where Δt f is the fluid timestep and Δl is the minimum fluid cell length.…”
Section: Simulation Programmentioning
confidence: 99%
“…Previous experimental and theoretical studies on suffusion have revealed that the erodibility of gap-graded soil is significantly influenced by confining pressure (p′) and fines content (F c ). [1][2][3][4][5][6][7][8][9][10][11][12][13][14] It was concluded from some studies that a higher confining F I G U R E 1 (A) Illustration of internal erosion and (B) schematic diagram of coarse grid DEM-CFD simulation approach adopted in this study pressure (p′) may help to prevent the occurrence of suffusion, due to the resulted increase in the interparticle contact force and particle connectivity. 8,9,15,16 Conversely, it was revealed from other studies that an increasing confining pressure could have intensified the suffusion (e.g., more fines loss) of a gap-graded soil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The granular soils under deviatoric stress path experience particle breakage and their critical state line (CSL) in e ‐ σ n plane move toward the lower void ratio 35,36 . The CSL translation has been simulated differently in previous studies 2,37–42 . In the proposed interface constitutive model, the effect of particle breakage in interface area is taken into account by translating downward the CSL in the e ‐ σ n plane through the determination of the reference critical void ratio ( e ref ) using the approaches by Liu et al 43 as given in Equation (11).…”
Section: Development Of a Nonlinear Incremental Soil‐structure Interface Modelmentioning
confidence: 99%
“…Multiphase flow through porous, deformable media occurs in a variety of applications in science and engineering 1–4 . In geotechnical engineering, predicting the increase of soil saturation due to rainfall infiltration is key to accurate modeling of landslide triggering 5–12 .…”
Section: Introductionmentioning
confidence: 99%